2014
DOI: 10.1002/jib.126
|View full text |Cite
|
Sign up to set email alerts
|

Application of a hop by-product in brewing: reduction in the level of haze-active prolamines and improved antioxidant properties of the beer

Abstract: After supercritical CO 2 extraction of hops or formation of lupulin-enriched pellets (type 45), polyphenol-rich by-products remain. These have some industrial and agricultural applications (preparation of polyphenol extracts and in the production of low-bitterness beers). In this work, both materials were used in pilot-scale brewing experiments for the production of beer enriched with polyphenols. Samples of beer made from these residues underwent analyses for haze-active prolamines, total polyphenols, phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Ferulate originates from malt, and is released during the mash most effectively at 45 °C , which was the mash‐in temperature used in this study. Ferulate has been characterized in hop extracts ; however, analysis of the aqueous fraction of hop extracts in this study revealed no measurable ferulate (data not shown) at the micromolar detection limit of NMR. Myrcene is one of most abundant molecules found in hop oil and was the only hop aroma compound that was able to be identified in this work.…”
Section: Resultsmentioning
confidence: 56%
“…Ferulate originates from malt, and is released during the mash most effectively at 45 °C , which was the mash‐in temperature used in this study. Ferulate has been characterized in hop extracts ; however, analysis of the aqueous fraction of hop extracts in this study revealed no measurable ferulate (data not shown) at the micromolar detection limit of NMR. Myrcene is one of most abundant molecules found in hop oil and was the only hop aroma compound that was able to be identified in this work.…”
Section: Resultsmentioning
confidence: 56%
“…Polyphenolic pellets (residue after manufacturing of Saaz hop) contain technologically promising phenolics (flavan‐3‐ols, flavonols, phenolic acids etc. ), but also a relatively large amount of sensory active compounds, particularly resins and essential oils . Furthermore, polyphenolic pellets also contain technologically inert compounds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The hot water extract for analyses of total polyphenols and analyses of total oils were performed according to Jelínek et al . .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations